STUDI PERBANDINGAN KOMPETENSI GURU LAKI-LAKI DAN PEREMPUAN BERDASARKAN PERSEPSI SISWA SMK NEGERI 5 PEKANBARU - Ditra Verbina Gurusinga; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of the research is that there are several characteristics of the differences in the competencies of male and female teachers in SMK Negeri 5 Pekanbaru. The formulation of the problem in this study is how to compare the competencies of male and female teachers based on student perspectives in SMK Negeri 5 Pekanbaru. The purpose of this study was to determine differences in the competencies of male and female teachers based on student perspectives in SMK Negeri 5 Pekanbaru. This research method is Quantitative with data collection instruments used namely questionnaire consisting of 28 questions and 3 indicators for male and female teachers. The population in this study were students SMK Negeri 5 Pekanbaru. Data management techniques used in this study using SPSS test t different. The study was conducted from January to February 2020 and based on the t test table, a comparison between male and female teacher competencies based on student perceptions SMK Negeri 5 Pekanbaru. is -0.229 with probability (sig.) 0.615. Because the probability (sig.) 0.615 <0.05 then Ha is rejected and t arithmetic -.0.229 smaller than t table 1.98027 (with df 118 and significant 5%). This means that there is no difference between male and female teacher competency based on perception SMK Negeri 5 Pekanbaru.Key Words: Teacher Competencies, Male Teachers and Female Teachers, Student Perceptions